Pengaruh Kerja Keras terhadap Hasil Belajar Siswa IPA di SMAN 1 Kota Jambi - Riska Fitriani; Wita Ardina Putri; Endah Febri Setya Rini; Nanda Hasbullah Sehab; Maharani Rizky Pratiwi (Universitas Indraprasta PGRI Jakarta, 2021)
The difficulty of increasing the character of learning hard work in a person can affect the learning outcomes, by increasing the effort to work hard in learning can have an impact on increasing student learning outcomes. The purpose of this study is to obtain a specific description of the effect of hard work on learning outcomes of physics through rotational dynamics and rigid object equilibrium at SMAN 1 Jambi City. The type of research used was quantitative research with survey research. The subjects in this study were 40 science students of class XI at SMAN 1 Kota Jambi held in October 2020. The instrument used by the researcher was a questionnaire containing 25 items about hard work, and 25 items for multiple choice questions. The data were obtained by distributing questionnaires and multiple choice questions to science students of class XI at SMAN 1 Jambi City, then the collected data were processed and analyzed using the IBM SPSS Statistics 23.0 program. The results showed that there was a significant effect of learning hard work on the learning outcomes of science students in class XI SMAN 1 Jambi City with a significance value of 0.000 <0.05, in other words, the more positive (the higher) a person's learning hard work towards physics lessons, the higher learning outcomes were obtained.